DAMPAK ALIRAN INVESTASI DAN BARANG/JASA PARIWISATA INTERNASIONAL TERHADAP PERMINTAAN PARIWISATA INDONESIA - Santi, Faurani (Jurnal Bisnis Darmajaya, 2016)
The purpose of this study to analyze the impact of international tourism  investment, goods/services to Indonesia tourism of demand, which used a Panel Least Square method and cross section data period 1990 - 2012 from  6 samples of countries (USA, Japan, ASEAN, Australia, the European Union, and Rest of the World). The  Panel Least Square (PLS) method analyzed the impact of international investment, and trade flows  to the Indonesia tourism demand; and the results obtained as follows: (1) amount of visits by foreign tourists, foreign tourists per visit consumption, investment demand are the most  impact to demand side of tourism in Indonesia, where per capita income of tourists origin country, price of Indonesian tourism, value of the inflow/outflow of goods/services of the Indonesian tourism are factors that affect the amount of tourist arrivals, tourist consumption, and  investment demand as components of tourism Indonesian tourism demand, (2) The economy leakage impact to the international flows of  investment, and trade in Indonesia , and (3) the development of tourism sector  (demand side) in Indonesia influenced by economic conditions (domestically and internationally), and macroeconomics stabilitization. Keywords: tourism investment flows, inflow, outflow, demand sides of tourism, and Impact